2015
DOI: 10.11604/pamj.2015.22.68.6228
|View full text |Cite
|
Sign up to set email alerts
|

Client perception of service quality at the outpatient clinics of a General hospital in Lagos, Nigeria

Abstract: IntroductionService quality assessments have assumed increasing importance in the last two decades. They are useful in identifying gaps in services been provided with the ultimate aim of guaranteeing quality assurance. The objective of this study was to assess the client perception of service quality at the outpatient clinics of Randle General hospital, Lagos.MethodsA descriptive cross sectional study was conducted from March to May 2013. A multistage sampling technique was used to select respondents and data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 16 publications
7
27
1
6
Order By: Relevance
“…12 A study of client perception of service quality at outpatient clinics of a general hospital in Lagos reported that 88% rated the overall service quality to be good with the assurance domain as the most important predictor (p <0.001) of service quality. 13 Amole et al in their study of patients perception of service quality in six teaching hospitals in southwest Nigeria reported that the most important factor to patients was the reliability dimension, followed by the assurance dimension with the empathy dimension being the least important factor. 14 This contrasts with another study by Oyatoye et al who studied four general hospitals in Ogun Sate and found that patients had the greatest preference for empathy while the least preference was waiting time.…”
Section: Introductionmentioning
confidence: 99%
“…12 A study of client perception of service quality at outpatient clinics of a general hospital in Lagos reported that 88% rated the overall service quality to be good with the assurance domain as the most important predictor (p <0.001) of service quality. 13 Amole et al in their study of patients perception of service quality in six teaching hospitals in southwest Nigeria reported that the most important factor to patients was the reliability dimension, followed by the assurance dimension with the empathy dimension being the least important factor. 14 This contrasts with another study by Oyatoye et al who studied four general hospitals in Ogun Sate and found that patients had the greatest preference for empathy while the least preference was waiting time.…”
Section: Introductionmentioning
confidence: 99%
“…In a district of Pakistan, the health service investigated with the use of SEVQUAL was poorly evaluated by the users. In Saudi Arabia, users were dissatisfied with all dimensions of sa-tisfaction of SERVQUAL over nursing services [11,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…In measuring patients' perceived health information management personnel service quality, the researchers modified an existing SERVQUAL scale as developed by Parasuraman et al (Parasuraman et al, 1988) and as adapted by similar studies assessing patients' perceived service quality (Essiam, 2013;Kazemi et al, 2013;Ogunnowo et al, 2015). The SERVQUAL scale is based on the five dimensions of service quality: reliability, gjhs.ccsenet.org…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, a study assessing patients' assessment of dental care services in a Nigerian hospital revealed there were marked statistically significant quality gaps in assurance and tangibles (Adebayo, Adesina, Ahaji, & Hussein, 2014). Also, a study conducted in a general hospital in Lagos, Nigeria, revealed that majority of the patients rated the overall service quality as good, while the assurance domain was revealed to be the most important predictor of perceived service quality (Ogunnowo, Olufunlayo, & Sule, 2015).…”
Section: Introductionmentioning
confidence: 99%